2021
DOI: 10.3390/jcm10235519
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Utilizing Telemedicine during and after the COVID-19 Pandemic: An Internet-Based International Study

Abstract: The COVID-19 pandemic challenges healthcare services. Concomitantly, this pandemic had a stimulating effect on technological expansions related to telehealth and telemedicine. We sought to elucidate the principal patients’ reasons for using telemedicine during the COVID-19 pandemic and the propensity to use it thereafter. Our primary objective was to identify the reasons of the survey participants’ disparate attitudes toward the use of telemedicine. We performed an online, multilingual 30-question survey for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Our findings of the reasons for TCs utilization are consistent with the motivations described in previous studies, these being “Non-Queue Requests” such as the convenience of e-records, e-referrals, and remotely issued sick leave; time saving; emergencies [ 63 ]; and economic factors [ 49 ]. The responses to the open-ended questions indicate that TCs have been mainly regarded as useful in emergencies or, conversely, in situations where the physician knows the patient, and the consultation is of a follow-up nature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings of the reasons for TCs utilization are consistent with the motivations described in previous studies, these being “Non-Queue Requests” such as the convenience of e-records, e-referrals, and remotely issued sick leave; time saving; emergencies [ 63 ]; and economic factors [ 49 ]. The responses to the open-ended questions indicate that TCs have been mainly regarded as useful in emergencies or, conversely, in situations where the physician knows the patient, and the consultation is of a follow-up nature.…”
Section: Discussionsupporting
confidence: 89%
“…Our respondents’ previous experience with TCs was not statistically significant for their current interest in using them. Previously, an international study [ 63 ] showed that TM use before the COVID-19 pandemic did not always increase the level of interest in its use after the pandemic. Further studies regarding the experiences and satisfaction with TM services among Polish PwDs could provide a deeper insight into patients’ attitudes towards TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients were younger working women of childbearing age. This gender ratio might be explained by women being overrepresented in the use of the internet and telemedicine [ 11 , 15 ] and because time-saving is a major factor for telemedicine usage [ 31 ]. Appointments within 48 hours, convenient health care access comparable to private practice, and flexibility could all contribute considerably to patient satisfaction and acceptance of the Consult Station health care system, as reported with other telemedicine devices [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family members who have used telemedicine services substantially impact consumers' intentions to participate in using them in the future. 29 Family support also affects consumer acceptance of technological developments through decisions on telemedicine services, 30 while the reference group shows results that do not affect consumer decisions in telemedicine services (p=0.193). This is not in line with previous research, which stated that social groups or reference groups influenced consumers to use telemedicine services.…”
Section: Resultsmentioning
confidence: 98%